Use of branched chain amino acids for treating hepatic encephalopathy: clinical experiences. (November 1986) - Rossi Fanelli, F; Cangiano, C; Capocaccia, L; Cascino, A; Ceci, F; Muscaritoli, M; Giunchi, G
Abstract : The efficacy of branched chain amino acids in two consecutive clinical studies in patients with severe hepatic encephalopathy was tested. In the preliminary uncontrolled study 19 patients with grade 3-4 hepatic encephalopathy were given an intravenous solution containing leucine 11 g/l, isoleucine 9 g/l, and valine 8.4 g/l in 20% dextrose. A complete recovery of mental state was obtained in all patients in a mean time of 20.5 hours. In a subsequent controlled study 40 patients with grade 3-4 hepatic encephalopathy were randomly assigned to receive intravenous branched chain amino acid in 20% dextrose (group A) or oral lactulose (group B). Twelve patients (70.6%) in group A and eight (47%) in group B regained consciousness in a mean time of 27.6 and 31.5 hours, respectively. The difference in the recovery rate between the two groups, although evident, was not significant. Intravenous branched chain amino acids are thus at least as effective as lactulose in reversing hepatic coma. These data argue strongly in favour of a therapeutic effect of branched chain amino acids in the treatment of hepatic encephalopathy in patients with chronic liver failure.